Polysaccharide-based Nanoparticles for Gene Delivery - Huh, Myung Sook; Lee, Eun Jung; Koo, Heebeom; Yhee, Ji Young; Oh, Keun Sang; Son, Sohee; Lee, Sojin; Kim, Sun Hwa; Kwon, Ick Chan; Kim, Kwangmeyung (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
Nanoparticles based on nanotechnology and biotechnology have emerged as efficient carriers for various biopharmaceutical agents including proteins and genes. In particular, polysaccharides have attracted interest of many researchers in the drug delivery field due to their advantages such as biocompatibility, biodegradability, low toxicity, and ease of modification. A number of polysaccharides including chitosan, hyaluronic acid, and dextran, and their derivatives have been widely used as polymeric backbones for the formation of nanoparticles, which can be provided as valuable gene delivery carriers. In this review, we introduce the chemical and physical natures of different polysaccharides particularly used in biomedical applications, and then discuss recent progress in the development of polysaccharide-based nanoparticles for gene delivery.
Keywords: GLYCOL CHITOSAN NANOPARTICLES; SMALL INTERFERING RNA; CONTROLLED DRUG-DELIVERY; ENDOTHELIAL GROWTH-FACTOR; MYELOID CELL LEUKEMIA-1; TUMOR-BEARING MICE; IN-VIVO DELIVERY; SIRNA DELIVERY; TARGETED DELIVERY; SYSTEMIC DELIVERY